2007
DOI: 10.1523/jneurosci.4494-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

β1 Integrins in Radial Glia But Not in Migrating Neurons Are Essential for the Formation of Cell Layers in the Cerebral Cortex

Abstract: Radial glial cells in the cerebral cortex serve as progenitors for neurons and glia and guide the migration of cortical neurons. The integrin ␣3␤1 is thought to mediate interactions of migrating neurons with radial glial cells and to function as a receptor for the reelin signaling molecule. Here, we challenge this view and demonstrate that ␤1 integrins in migrating neurons are not essential for the formation of cell layers in the cerebral cortex. Cortical cell layers also form normally in mice deficient in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(168 citation statements)
references
References 58 publications
13
154
1
Order By: Relevance
“…In agreement, the amount of phosphorylated focal adhesion kinase (pFAK) at T397, an active form of FAK, was decreased in Itgb1 f/f ; Emx1-Cre mice (Supplementary information, Figure S7), suggesting the inhibition of integrin-mediated focal adhesion signaling. Consistent with previous reports of restricted Itgb1 elimination in post-mitotic neurons [23,24], we found that both the cortex size and lamination were roughly normal in Itgb1 f/f ; Emx1-Cre or Itgb1 f/+ ; Emx1-Cre mice (Supplementary information, Figure S9). …”
Section: Itgb1 Is Required For Axon Formation In Cortical Neurons In supporting
confidence: 92%
See 1 more Smart Citation
“…In agreement, the amount of phosphorylated focal adhesion kinase (pFAK) at T397, an active form of FAK, was decreased in Itgb1 f/f ; Emx1-Cre mice (Supplementary information, Figure S7), suggesting the inhibition of integrin-mediated focal adhesion signaling. Consistent with previous reports of restricted Itgb1 elimination in post-mitotic neurons [23,24], we found that both the cortex size and lamination were roughly normal in Itgb1 f/f ; Emx1-Cre or Itgb1 f/+ ; Emx1-Cre mice (Supplementary information, Figure S9). …”
Section: Itgb1 Is Required For Axon Formation In Cortical Neurons In supporting
confidence: 92%
“…npg adhesion molecules are involved in initial neuritogenesis [20], neurite outgrowth and regeneration [21], axon path finding [22], neuronal positioning [23][24][25], as well as synaptic development and plasticity [26]. However, whether and how integrin-mediated cell adhesion is involved in neuronal polarization is unknown.…”
Section: Wen-liang Lei Et Al 955mentioning
confidence: 99%
“…A role for integrin ␤1 has also been demonstrated for the development of cortical and cerebellar radial glial cells, where it acts as an essential component of the endfeet anchorage to the external limiting membrane (Graus-Porta et al, 2001; Milner and Campbell, 2002;Belvindrah et al, 2007). We found that throughout development radial glial cells of the SCO express integrins ␣6 and ␤1, but not ␤3.…”
Section: Discussionsupporting
confidence: 66%
“…For instance, mice carrying mutations in integrin ␣6 and those lacking integrin ␤1 show defects in the anchorage of radial glial processes at the meningeal basement membrane in the cerebral and cerebellar cortex (Georges-Labouesse et al, 1998;Graus-Porta et al, 2001;Milner and Campbell, 2002;Belvindrah et al, 2007). On the other hand, integrins interact with the TSR domain of several members of the TSR superfamily (Leu et al, 2003;Calzada et al, 2004;Short et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based assays implicate c-Src, PI3 kinase, and ERK1/2 in the CHL1-integrin signaling pathway [12]. Integrins have been shown to participate in the mechanism of radial migration of embryonic cortical neurons [13] but appear to function when expressed on radial glia, rather than on neurons [14]. Thus, a trans heterophilic interaction between CHL1 on neurons, and β1 integrins on radial glia, may transduce signaling in migrating cortical neurons responsible for correct laminar positioning.…”
Section: L1 and Chl1 As Signaling Co-receptors In Cortical Developmentmentioning
confidence: 99%